DEVELOPMENT OF ENDOCARDITIS IN DENTISTRY AND THE IMPORTANCE OF ORAL HYGIENE: LITERATURE REVIEW - Natália Franco Brum; Mariana Sobreira Bezerra; Flávia Kolling Marquezan; Patricia Kolling Marquezan; Aline Sobreira Bezerra (Revista Naval de Odontologia On Line, 2021)
Bacterial endocarditis (BE) is an infectious disease with several etiological factors, including the constant presence of oral bacteria. Given this relationship and the relevance of the subject, it is essential that dentists deepen their knowledge on this matter. Thus, the aim of the study is to conduct a literature review on the mechanism of BE development and its relationship with oral hygiene. Searches were conducted in the PubMed, EMBASE and Biblioteca Virtual em Saúde (BVS) platforms, using the descriptors previously selected from the MeSH and DeCS platforms. After analyzing their titles and abstracts and then read in full, nine articles were selected for the literature review. The findings show that poor oral hygiene in individuals with cardiovascular disorders may be a predisposing factor for the development of BE, due to the interaction of microorganisms and pro-inflammatory mediators. Therefore, the understanding that maintenance of oral hygiene is essential to reduce microbial accumulation and aggregation and, consequently, BE, highlights the importance of dentists knowing the subject to prevent complications and act preventively.